Challenges and Opportunities of Microfinance in Nepal - Karn, Santosh Kumar (International Journal of Social Sciences and Management, 2018)
The purpose of the paper is to highlight the opportunities and challenges faces the microfinance sector in Nepal. Many developmental programs implemented in Nepal, microfinance programs have a strong rural orientation and are targeted at the poor. Numerous challenges are ahead of this sector like lack of accessibility, unhealthy competition, seasonal migration, political unawareness, excluding vulnerable groups, threatening the financial discipline, resource constraints, low level of knowledge. of micro finance institutions (MFIs) etc. On the other hand, the rapid increase in poverty in Nepal, along with other opportunities, is paving way for the growth of this sector and offering a huge market potential for microfinance. On this basis the sector presents a lot of opportunities such as: stimulating growth of economy, women empowerment, increasing volume, accessibility and outreach, economics of scope etc. Int. J. Soc. Sc. Manage. Vol. 5, Issue-3: 72-75